2008
DOI: 10.1073/pnas.0809218105
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteomics of phagosomes suggests a connection to autophagy

Abstract: Phagocytosis is the central process by which macrophage cells internalize and eliminate infectious microbes as well as apoptotic cells. During maturation, phagosomes containing engulfed particles fuse with various endosomal compartments through the action of regulatory molecules on the phagosomal membrane. In this study, we performed a proteomic analysis of the membrane fraction from latex bead-containing (LBC) phagosomes isolated from macrophages. The profile, which comprised 546 proteins, suggests diverse fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 42 publications
7
114
1
Order By: Relevance
“…After cell disruption using 30-gauge needle syringes, the latex bead containing phagosomes were isolated on a sucrose gradient (52,53). The isolated phagosome was washed and resuspended with serum-free media for further use in experiments.…”
Section: Methodsmentioning
confidence: 99%
“…After cell disruption using 30-gauge needle syringes, the latex bead containing phagosomes were isolated on a sucrose gradient (52,53). The isolated phagosome was washed and resuspended with serum-free media for further use in experiments.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown previously that phagosome isolated by flotation display low levels of contamination (40). The recent finding that phagosomes extensively interact with autophagosomes (41,42) suggests that this type of interaction would bring a wide variety of proteins to the phagosome lumen for degradation. Interestingly, we observed that phagosomes isolated from cells displaying high levels of autophagic activity contained higher levels of the aforementioned types of proteins (unpublished observations).…”
Section: Fig 1 Validation Of the Phagosome Drms Isolation And The Rmentioning
confidence: 99%
“…Proteomic analysis of isolated phagosomal membranes from naïve uninfected macrophages revealed the presence of LC3, the level of which increases in response to starvation-induced autophagy. This result suggests a direct relationship between phagocytosis and autophagy, and possibly a more general role for LAP in the physiology of macrophages (74). Indeed, LAP plays an important role in the autoimmune response by efficient phagocytic clearance of apoptotic cells (72).…”
Section: Yersinia Pseudotuberculosismentioning
confidence: 87%